Edge Detection For Medical Images Using Threshold Based on Genetic Algorithm - Saleh, Kawther Thabt (MAGISTRA, 2016)
In computer vision applications it is essential to detect objectâs edges specialty in medicalimage applications. In this proposed paper threshold is used based on genetic algorithm to detect the object edgefor medical images. In the proposed algorithm, there are principles for generating useful solutions to theoptimization and the look for objects. Furthermore, the results of sobel, canny filters and genetic algorithm arecompared with the results of the proposed approach to detect objects for medical images.Keywords: threshold, genetic algorithm, edge detection, medical image